Kepadatan Spora Jamur Mikoriza Vesikular Arbuskular Pada Tiga Tingkat Kematangan Gambut Di Kawasan Hutan Lindung Gunung Ambawang Kabupaten Kubu Raya - Siti Khotimah, Friska Sianturi, Riza Linda, (Universitas Tanjungpura, 2015)
The mycorrhiza is a microorganism which is symbiotic with plant roots, in which it helps plants to absorb nutrients. The mycorrhiza had no effect on fertile soil, but plays an active role in the less fertile soil, one of which is peat soil. Based on its level of ripening, peat soil can be divided into three categories, i.e. sapric, hemic and fibric. This research was conducted to find out the types of spores of vesicular arbuscular mycorrhiza (VAM) and the density of VAM spores at three levels of peat ripening in the area of Gunung Ambawang protected forest in Kubu Raya Regency. This research was conducted for six months from November 2014 to April 2015 in the Laboratory of Microbiology, Faculty of Mathematics and Natural Sciences of Tanjungpura University. The soil sample was taken in the area of Gunung Ambawang protected forest and the analysis of soil chemical content was carried out in the Laboratory of Chemistry and SoilFertility, Faculty of Agriculture of Tanjungpura University. The isolation of spores was done through a combined method of wet-sieving technique and centrifugation technique. The results indicated that the spores found consisted of 6 genera i.e. Acaulospora, Archaeospora, Gigaspora, Glomus, Paraglomus andSclerocystis. The spore density was the highest in sapric peat with 558 spores, medium density in hemic peat with 514 spores, and the lowest density in fibric peat with 393 spores.